Ankle‐Brachial Index Testing at the Time of Stress Testing in Patients Without Known Atherosclerosis. Issue 1 (22nd December 2015) - Narula, Amar; Benenstein, Ricardo J.; Duan, Daisy; Zagha, David; Li, Lilun; Choy‐Shan, Alana; Konigsberg, Matthew W.; Lau, Ginger; Phillips, Lawrence M.; Saric, Muhamed; Vreeland, Lisa; Reynolds, Harmony R.
Abstract: Background: Individuals referred for stress testing to identify coronary artery disease may have nonobstructive atherosclerosis, which is not detected by stress tests. Identification of increased risk despite a negative stress test could inform prevention efforts. Abnormal ankle‐brachial index (ABI) is associated with increased cardiovascular risk. Hypothesis: Routine ABI testing in the stress laboratory will identify unrecognized peripheral arterial disease in some patients. Methods: Participants referred for stress testing without known history of atherosclerotic disease underwent ABI testing (n = 451). Ankle‐brachial index was assessed via simultaneous arm and leg pressure using standard measurement, automated blood‐pressure cuffs at rest. Ankle‐brachial index was measured after exercise in 296 patients and 30 healthy controls. Abnormal postexercise ABI was defined as a >20% drop in ABI or fall in ankle pressure by >30 mm Hg. Results: Overall, 2.0% of participants had resting ABI ≤0.90, 3.1% had ABI ≥1.40, and 5.5% had borderline ABI. No patient with abnormal or borderline ABI had an abnormal stress test. Participants who met peripheral arterial disease screening criteria (age ≥65 or 50–64 with diabetes or smoking) tended toward greater frequency of low ABI (2.9% vs 1.0%; P = 0.06) and were more likely to have borderline ABI (0.91 to 0.99; 7.8% vs 2.9%; P = 0.006). Postexercise ABI was abnormal in 29.4% of patients and 30.0% of controls ( P not significant). Conclusions: Ankle‐brachial index screening at rest just before stress testing detected low ABI in 2.0% of participants, all of whom had negative stress tests.